Use of Chest X-Ray (CXR) in Covid-19 Screening as A Modalities: Covid-19 Screening - Prabowo, Adityo (CoinReads Media Prima, 2022)
Background: As of March 11, 2020, the number of confirmed cases in China had reached 80,955 with the death toll reaching 3,162. So far, Covid-19 tends to infect people who have comorbid diseases such as heart disease, diabetes mellitus, cancer and chronic respiratory diseases as well as people over 60 years of age. Several cases of Covid-19 have also been reported in pregnant women. Method: Radiographic technologies and tools including chest X-Ray and Computed Tomography (CT) are applied for initial screening and the follow-up because they provide detailed diagnoses with specific pathological features for staging and treatment settings. Not infrequently cases of Covid-19 are found in pregnant women because during pregnancy women’s condition becomes very vulnerable to infection with pneumonia pathogens due to physiological changes during pregnancy that result in a decrease in the immune system. Although the clinical symptoms are the same as for non-pregnant women and there are no aggravating factors, pregnant women are prone to hypoxia. Results: Chest x-ray (CXR) is a radiographic projection tool that can help diagnose conditions or abnormalities in the thoracic cavity. Due to the spread of Covid-19, it is important to recognize the common Covid-19 imaging findings and the abnormal pneumonia that occurs over time on CXR results. CXR can be used to diagnose patients with acute respiratory distress as the first line of evaluation for Covid-19 patients 19. Conclusion: CXR can be a screening modality in Covid-19 patients including pregnant women. However, it is necessary to keep in mind that the CXR examination can have an impact on the fetus. Even though the risk is small, pregnant women who will undergo a Covid-19 examination or evaluation need special attention. In addition, it is necessary to consider other examinations that can be carried out especially on pregnant women, which do not have the effect of radiation